TEFL in the Postmethod Era - Surya Asra; Faizatul Husna; Fadlia Fadlia; Allif Syahputra Bania (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2022)
This study aims to review the implementation of steps in teaching English as a Foreign Language (TEFL) from a post-method point of view. The research is an analytical study using a literature review approach to describe the results and to draw conclusions. The results of the literature analysis show that basically there is no fundamental theoretical difference between the method and post-method. Regarding the implementation of teaching English from the post - method point of view, there is no fundamental difference found on the steps of teaching English in methods that existed before the era of post-method. Therefore, the energy of debate between proponents of method and post-method can be directed to find the best and appropriate steps in teaching English to students.